(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Brigada Eskwela, a program of the Department of Education for the maintenance of schools, aims to bring together all education stakeholders to participate and contribute their time, effort, and resources to prepare public school facilities for the opening of each school year, thereby addressing the challenges of public schools in the Philippines. Fortunately, this worthy endeavor opened multiple doors for learning and reflection by allowing everyone to contribute. This descriptive research assessed the SY 2017-2018 outstanding Brigada Eskwela program implementers among the San Fernando City Division’s different school categories. Using g*power in determining the sample size, there were 132 representatives randomly selected from each of the four groups of respondents (school heads and teachers, parents and pupils, private and government partners, and barangay officials, giving a total of 528 respondents. The data gathered were managed using descriptive and inferential statistics. The findings revealed that a) the Brigada Eskwela Program objectives were very highly attained, the activities were very highly implemented, and the program was very highly participated by different groups; b) the different groups of respondents were impacted differently by the Bridaga Eskwela program; and c) a significant inverse relationship was felt on the attainment of BE objectives with the participation, implementation, and the impact of the program on the implementers; and the involvement of the stakeholders on the implementation of the BE program. The findings highlighted interesting viewpoints with the implementation of the Brigada Eskwela as a mechanism of making all education stakeholders come together working for the common good in pursuit of the delivery of quality education for the learners. Consequently, the Brigada Eskwela Implementation Model was crafted and endorsed for adoption.